Біологічні та біохімічні особливості маслинки багатоквіткової (Elaeagnus multiflora Thunb.) в Лісостепу України - Moroz, P.A.; Vasjuk, E.A.; Dzhurenko, N.I.; Palamartchuk, O.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
This paper presents some morphological characteristics of Elaeagnus multiflora Thunb. and the results perspective forms, and gives the dynamics of ascorbic acid, flavone and tannin accumulation in leaves and shoots.